Effect of maximal exercise on the electrophysiological evaluation of leg muscles in young healthy males - Hamod, Asmaa’ K.; Sulaiman, Shakir M.; Salih, Istabrak M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Bicycling is a type of aerobic exercise that it is beneficial for the health of cardiovascular, pulmonary, and musculoskeletal systems .In this study, utilization of some of electrophysiological tests is to assess changes , from the functional point of view, in the peripheral nerves & their muscles that occur in relation to maximal exercise. patients & methods: 100 young healthy males , age (18-35) years old, were collected during the period from 1st of April to 1st of October 2008 at the department of neurophysiology in the Ibn Sinna teaching hospital , Mosul city. They underwent electroneurographic assessment of common peroneal & tibial nerves, in addition to electromyographic assessment of Tibialis Anterior & Gastrocnemius muscles before & after exercise challenge test on bicycle ergometer. Results: In this study, there is a higher value regarding compound motor action potential amplitudes & motor conduction velocity of both nerves, with increase in the values of motor unit potential amplitudes & interference pattern of both muscles post exercise in comparison to the pre exercise. In addition, there is positive correlation between MUP amplitude of Gastrocnemius muscle & tibial nerve. Conclusion : the results indicates that within this age group the exercise challenge test leads to increase in the force produced with no signs of muscular fatigue electrophysiologically .